The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1475921714560073
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous and local wavenumber estimations for damage quantification in composites

Abstract: The continued and expanded use of composite materials in aerospace applications necessitates structural health monitoring and/or nondestructive evaluation techniques that can provide quantitative and detailed damage information for layered plate-like components (such as composite laminates). Guided wavefield methods are at the basis of a number of promising techniques for the detection and the characterization of damage in plate-like structures. Among the processing techniques that have been proposed for guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 33 publications
1
60
0
1
Order By: Relevance
“…Early efforts considered "snapshot" visualization [22] as well as accumulated energy plots [23]. Other approaches include standing wave analysis [6], wavenumber filtering [24], instantaneous wavenumber techniques [25][26][27], anomaly detection via dictionary learning [28], and a combined beamforming and wavenumber analysis technique [29], although this list is certainly not inclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts considered "snapshot" visualization [22] as well as accumulated energy plots [23]. Other approaches include standing wave analysis [6], wavenumber filtering [24], instantaneous wavenumber techniques [25][26][27], anomaly detection via dictionary learning [28], and a combined beamforming and wavenumber analysis technique [29], although this list is certainly not inclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, full time-space wavefields of guided waves, measured by non-contact laser Doppler vibrometers, have been extensively studied for use in damage detection [6][7][8][9][10][11][12]. The various methods developed to process full wavefield data for damage detection include: amplitude based imaging, wave filtering based imaging, and wavenumber based imaging, among others [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Wavenumber based imaging uses intrinsic wavenumber information obtained from the full wavefields for quantitative evaluation of the defects in metals and laminated composites [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The various methods developed to process full wavefield data for damage detection include: amplitude based imaging, wave filtering based imaging, and wavenumber based imaging, among others [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Wavenumber based imaging uses intrinsic wavenumber information obtained from the full wavefields for quantitative evaluation of the defects in metals and laminated composites [18][19][20][21][22][23][24]. It has been shown that wavenumber information can be used not only to detect the damage location, but also to quantify the damage size, shape and depth [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…These methods commonly address mapping flaws by recording the wave propagation over a finite span of the wavefield, rather than measurements at a single point. These methods reduce the wavefield through wavenumber filtering [11][12][13] to identify damage, or exploit changes in the propagating wave's characteristic over a delamination to locate the flaw [14,15].…”
Section: Introductionmentioning
confidence: 99%